Transformational Leadership During the COVID-19 Pandemic: Strengthening Employee Engagement Through Internal Communication - Santoso, Nobertus R.; Sulistyaningtyas, Ike D.; Pratama, Brahma P. (The Journal of communication inquiry, 2022)
This article examines the function of transformational leadership in enhancing employee engagement through internal communication during the COVID-19 pandemic to ensure the companies’ sustainability. This article is based on semi-structured interviews with 16 informants (human resources department representatives and employees) from the four industries most impacted by the COVID-19 epidemic: travel, hotel, food and beverage, and retail sectors. The findings reveal that transformational leaders play a critical role in fighting the COVID-19 pandemic by encouraging employees to be innovative and creative, undertaking active actions, and strengthening employee engagement through internal communication. On the other hand, internal communication has changed due to the pandemic, including communication flow, messages, and media. Internal communication has promoted a climate for active communication behaviors encouraging knowledge sharing, collaboration, and creativity-enhancing employee engagement. Through spiritual values, transformational leaders who promote employee engagement amid this crisis ensure the organization's sustainability. Due to the COVID-19 pandemic, this research suggests that leaders might increase employee engagement by including spiritual values through internal communication.